Composite conductive film and preparation method and application thereof
By combining POMs@M nanoparticles with PEDOT, a new light-responsive conductive film was constructed, which solved the problems of low photocurrent and poor aqueous solution stability of traditional PEDOT materials, and achieved efficient photo-electric conversion and charge transfer efficiency.
Patent Information
- Application Number
- CN202510333191.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
AI Technical Summary
The photocurrent performance of traditional PEDOT materials is limited, the aqueous solution is poor, and the charge transfer efficiency of POMs and conductive materials is insufficient. The synergistic effect of metal nanoparticles and POMs has not been fully developed.
By compounding POMs@M nanoparticles with PEDOT, a new light-responsive conductive film was constructed, and the redox activity of POMs and the catalytic synergistic effect of metal nanoparticles was achieved in high-efficiency photo-electric conversion under the condition without sacrificial agent. The specific method includes preparing Zn4P4W30@M nanoparticles and forming a PEDOT/Zn4P4W30@M film on the ITO glass sheet by electropolymerization.
The photocurrent performance and aqueous solution stability of traditional PEDOT materials are improved, the charge transfer efficiency of POMs and conductive materials is enhanced, and the synergy between metal nanoparticles and POMs is fully developed to achieve efficient photo-electric conversion.
Smart Images

Figure CN119852031A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new materials and new energy, and specifically relates to a composite conductive film and a preparation method and application thereof. Background Art
[0002] Polyoxometalates (POMs) are transition metal oxygen anion clusters with d0 electronic configuration that exhibit photocatalytic behavior similar to that of semiconductor metal oxides. Under light irradiation, electrons rise from an oxygen-centered 2p orbital to an empty metal d orbital, generating a highly active charge-separated state. Based on this concept, Anandan et al. impregnated POM in polyvinylidene fluoride polymer as a solid polymer electrolyte in dye-sensitized solar cells and obtained promising results. The above excellent properties and pioneering research indicate that POM will be an ideal candidate material for optimizing electrolyte efficiency during photocurrent generation. Otherwise, in the presence of sacrificial electron donors, photolysis will reduce POMs, which in turn leads to the reduction of metal ions, and ultimately becomes an effective alternative method for the synthesis and recovery of metal nanoparticles.
[0003] Polyoxometalates@M nanoparticles-dye nanostructured materials combine excellent properties and various functions, and may be an attractive approach for energy applications. On the other hand, an important point for many real-life technologies is the charge exchange between the chemical reaction center and the external circuit. Depending on the POMs cluster, as the connecting line between the highly redox-active molecules and the external circuit, the requirements for conductive materials are high. Conductive polymers are a breakthrough organic conductive material with important application value in electronic and energy systems. The application of conductive polymers in energy conversion and storage has attracted widespread attention. Poly(3,4-ethylenedioxythiophene) (PEDOT for short) has excellent thermal and chemical stability, high conductivity, flexibility, low cost, high transparency, high carrier mobility and biocompatibility, so it has been widely used. In addition, PEDOT can also be doped with polyoxometalates for photovoltaic applications.
[0004] PEDOT is reported to be the most successful conductive polymer to date and is also currently available on the market. Due to its unique optoelectronic properties and excellent processing performance, it has a wide range of applications in energy conversion and storage devices. As mentioned above, the performance of PEDOT is highly dependent on the synthesis process, doping, post-processing, composite structure, morphology, etc. In most practical cases, the properties of PEDOT-based hybrid materials need to be customized to meet specific applications. With the continuous improvement of the performance of PEDOT composites, the discovery of new properties, the development of new composites or the continuous development of new applications such as perovskite solar cell buffer layers, it is believed that PEDOT composites will continue to be important electronic materials in modern technology.
[0005] The prior art has the following defects: The photocurrent performance of single PEDOT films is limited, the charge transfer efficiency between POMs and conductive materials is insufficient, the stability and adaptability challenges in aqueous environments, and the synergistic effect of metal nanoparticles and POMs have not been fully developed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a composite conductive film, which solves the problems of low photocurrent and poor stability of aqueous solution of traditional PEDOT materials, and at the same time utilizes the redox activity of POMs and the catalytic synergistic effect of metal nanoparticles to achieve efficient light-to-electricity conversion without sacrificial agents.
[0007] The present invention provides a method for preparing a composite conductive film, comprising: Step 1: Preparation of Zn4P4W 30 The solution was added with a metal salt solution of metal M, ultrasonically treated and argon was introduced, and a Zn4P4W-coated surface was prepared under ultraviolet light. 30 Metal M nanoparticles; Step 2: At a certain temperature, in an argon environment, 3,4-ethylenedioxythiophene is converted into poly (3,4-ethylenedioxythiophene) on the ITO glass sheet electrode through an electropolymerization reaction in an electrolyte solution to form a composite conductive film. The conductive film is formed by using Zn4P4W 30 The enclosed metal M nanoparticles are formed by the electropolymerization doping process; The conditions of the electropolymerization reaction are -0.88V~+1.10V vs. SCE, and the electropolymerization is carried out at a cycle rate of 100mV / s; the electrolyte solution is a sulfuric acid solution with a pH=1; and the metal M=Au, Pt, Pd.
[0008] The present invention also provides an application of the composite conductive film prepared above in terms of electrochemical redox performance.
[0009] Technical effects of the present invention: The present invention constructs a new type of light-responsive conductive film by compounding POMs@M nanoparticles with PEDOT (hereinafter referred to as PEDOT / POMs@M), which solves the problems of low photocurrent and poor stability of aqueous solution of traditional PEDOT materials. At the same time, the redox activity of POMs and the catalytic synergistic effect of metal nanoparticles are utilized to achieve efficient light-to-electricity conversion without sacrificial agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is an electropolymerization reaction diagram provided by an embodiment of the present invention; Figure 1Figure A) is a diagram of the electropolymerization reaction of EDOT alone provided by an embodiment of the present invention; Figure 1 B) is a diagram of EDOT on Zn4P4W provided by an embodiment of the present invention. 30 Electropolymerization reaction diagram in the presence of Zn4P4W 30 Metal M nanoparticles (abbreviated as Zn4P4W 30 @M) Electropolymerization reaction diagram in the presence of; Figure 2 It is Zn4P4W provided by the embodiment of the present invention 30 @UV-visible absorption spectrum measurement diagram of Pt formation process; Figure 2 A) Figure shows the Zn4P4W 30 @UV-visible absorption measurement during Pt formation; Figure 2 B) Figure 2 shows the Zn4P4W 30 @The change of absorbance in the UV-visible absorption spectrum at wavelength λ=425nm during the formation of Pt; Figure 2 C) Figure shows the Zn4P4W 30 @The change of absorbance in the UV-visible absorption spectrum at wavelength λ=730nm during the formation of Pt; Figure 3 It is Zn4P4W provided by the embodiment of the present invention 30 @UV-visible absorption spectrum measurement diagram during Au formation; Figure 3 A) Figure shows the Zn4P4W 30 @UV-visible absorption spectrum during Au formation; Figure 3 B) Figure shows the Zn4P4W of the present invention 30 @The absorbance diagram at wavelength λ=540nm during Au formation; Figure 3 C) Figure shows the Zn4P4W 30 @The absorbance diagram at wavelength λ=690nm during Au formation; Figure 4 The Zn4P4W of the present invention 30 UV-visible absorption measurement of @Pd; Figure 5 It is Zn4P4W provided by the embodiment of the present invention 30 Transmission electron microscopy (TEM) image of @Pt; Figure 5A) Figure 1 shows Zn4P4W provided in an embodiment of the present invention. 30 Transmission electron microscope (TEM) image of @Pt (image size scale is 50nm); Figure 5 B) is a diagram of Zn4P4W provided in an embodiment of the present invention. 30 Transmission electron microscope (TEM) image of @Pt (image size scale is 20nm); Figure 6 It is Zn4P4W provided by the embodiment of the present invention 30 @Transmission electron microscope (TEM) image of Au; Figure 6 A) Figure 1 shows Zn4P4W provided in an embodiment of the present invention. 30 @Transmission electron microscope (TEM) image of Au (image size scale is 100nm); Figure 6 B) is a diagram of Zn4P4W provided in an embodiment of the present invention. 30 @Transmission electron microscope (TEM) image of Au (image size scale is 50nm); Figure 7 Zn4P4W provided in the embodiment of the present invention 30 @Transmission electron microscopy (TEM) image of Pd; Figure 8 is an electropolymerization diagram provided by an embodiment of the present invention; Figure 8 A) is an electropolymerization diagram of a PEDOT film provided by an embodiment of the present invention; Figure 8 B) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 Electropolymerization diagram of Fig. 9 is an electropolymerization diagram of different thin films provided by embodiments of the present invention; Fig. 9 A) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Electropolymerization diagram of Pt thin film; Fig. 9 B) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Electropolymerization diagram of Au thin film; Fig. 9 Figure C) shows the PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Electropolymerization diagram of Pd film; Fig.10 PEDOT / Zn4P4W provided in the embodiment of the present invention 30 UV-Vis absorption graph during the formation process; Fig.11 This is a diagram of an electrochemical quartz crystal microbalance measurement provided by an embodiment of the present invention; Fig.11 A) is an electrochemical quartz crystal microbalance measurement diagram of PEDOT provided by an embodiment of the present invention; Fig.11 B) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 Electrochemical quartz crystal microbalance measurement diagram; Fig.12 An atomic force microscope (AFM) image of a PEDOT film provided by an embodiment of the present invention; Fig.13 PEDOT / Zn4P4W provided in the embodiment of the present invention 30 AFM image of the film, and schematic diagram of cross-section analysis marked with green lines on the 2D AFM image; Fig.14 PEDOT / Zn4P4W provided in the embodiment of the present invention 30 @AFM image of Pt film; Fig.15 is an AFM image provided by an embodiment of the present invention; Fig.15 A) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @One of the AFM images of Au thin film; Fig.15 B) is an EDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Au film zoomed-out display effect diagram; Fig.15 Figure C) shows EDOT / Zn4P4W provided by an embodiment of the present invention 30 @Au film magnified display effect diagram; Fig.15 D) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @AFM image 2 of Au thin film; Fig.16 [PEDOT / Zn4P4W provided in the embodiment of the present invention 30 ]nPhotoelectrochemical response diagram of different scanning times n (n=1~10) during the preparation process of the film; Fig.17 When n=5, PEDOT and PEDOT / Zn4P4W of the present invention 30 Photoelectrochemical response diagram of the film; Fig.18The embodiment of the present invention provides that when the number of electropolymerization iterative scans n is 5, PEDOT (black), PEDOT / Zn4P4W 30 (red), PEDOT / Zn4P4W 30 @Pd (green), PEDOT / Zn4P4W 30 @Pt (blue) and PEDOT / Zn4P4W 30 @Photoelectrochemical response diagram of Au (purple) film; Fig.19 is a photoelectrochemical response diagram of different films provided by the embodiments of the present invention under different electropolymerization scan times n; Fig.19 A) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Photoelectrochemical response diagram of Au film under different electropolymerization scan times n; Fig.19 B) is a PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Photoelectrochemical response diagram of Pt film under different electropolymerization scan times n; Fig.19 Figure C) shows the PEDOT / Zn4P4W provided in an embodiment of the present invention. 30 @Photoelectrochemical response diagram of Pd film under different electropolymerization scan times n; Fig. 20 The embodiment of the present invention provides that when the number of electropolymerization iterative scans n is 5, PEDOT / Zn4P4W 30 @Photoelectrochemical response diagram of Au film; Fig. 20 A) Figure shows different concentrations of Na + I3 - PEDOT / Zn4P4W 30 @Au]5 film photoelectrochemical response diagram; Fig. 20 B) Figure 2 shows the Na + I3 - Photocurrent variation diagram measured in aqueous solution (1~20.0mmol / L); Fig.21 The embodiment of the present invention provides that when the number of electropolymerization iterative scans n is 5, PEDOT / Zn4P4W 30 @Photoelectrochemical response diagram of Pt film; Fig.21 A) is a graph showing the electropolymerization of different concentrations (1-20.0 mmol / L) of Na when the number of iterative scans n is 5 provided in an embodiment of the present invention. + I3- PEDOT / Zn4P4W 30 @Pt photoelectrochemical response diagram; Fig.21 B) Figure 2 shows the Na concentrations (1-20.0 mmol / L) provided in the embodiments of the present invention. + I3 - Graph of photocurrent changes measured in aqueous solution. DETAILED DESCRIPTION
[0011] The invention is illustrated by the following examples.
[0012] The invention discloses a method for preparing a composite conductive film, comprising: Step 1: Preparation of Zn4P4W 30 The solution was added with a metal salt solution of metal M, ultrasonically treated and argon was introduced, and a Zn4P4W-coated surface was prepared under ultraviolet light. 30 Metal M nanoparticles (hereinafter referred to as Zn4P4W 30 @M); Step 2: At a certain temperature, in an argon environment, 3,4-ethylenedioxythiophene is converted into poly (3,4-ethylenedioxythiophene) on the ITO glass sheet electrode through an electropolymerization reaction in an electrolyte solution to form a composite conductive film. The conductive film is formed by using Zn4P4W 30 The metal M nanoparticles contained therein are used to carry out the electropolymerization doping process (hereinafter referred to as PEDOT / Zn4P4W 30 @M film); The conditions of the electropolymerization reaction are -0.88V~+1.10V vs. SCE, and the electropolymerization is carried out at a cycle rate of 100mV / s; the electrolyte solution is a sulfuric acid solution with a pH=1; and the metal M=Au, Pt, Pd.
[0013] Preparation of Zn4P4W 30 The solution includes: According to the type of metal M, prepare 4mL of Zn4P4W with corresponding concentration. 30 A solution containing 0.5 M isopropanol.
[0014] When metal M=Pt, Zn4P4W 30 The concentration of the solution is 6.4x10 -5 mol / L; When metal M=Au, Zn4P4W 30 The concentration of the solution is 8x10 -6 mol / L; When metal M=Pd, Zn4P4W 30 The concentration of the solution is 8x10-6 mol / L.
[0015] The metal salt solution to which the metal M is added includes: When metal M=Pt, it is Zn4P4W 30 Add 5 μL of 8 wt.% H2Pt to the solution. IV C l6 ; When metal M=Au, Zn4P4W 30 Add 5 μL of HAu with a concentration of 7.4 wt.% to the solution III Cl4; When metal M=Pd, Zn4P4W 30 Add 5 μL of the solution with a concentration of 1.28×10 -6 mol / L Pd II SO4 solution.
[0016] The ultrasonic treatment time was 20 minutes.
[0017] The argon gas was introduced for 30 minutes.
[0018] Before the electropolymerization reaction, it also includes: ITO glass sheet pretreatment; The ITO glass sheet was pretreated as follows: the ITO glass sheet was ultrasonicated with acetonitrile for 5 minutes, then carefully washed with methanol and ultrapure water three times, and dried in an oven.
[0019] Electropolymerization reactions include: Step 1: Prepare a Zn4P4W-coated substrate by photoinduction in an argon atmosphere at 25°C. 30 Metal M nanoparticles; Step 2: Cover the surface with Zn4P4W 30 The metal M nanoparticles are dispersed into a sulfuric acid solution (represented as H2SO4 in the figure) with a pH of 1 to form an acidic electrolyte solution containing the nanoparticles; Step 3: In the electropolymerization reaction, an ITO glass sheet or a pretreated ITO glass sheet is used as a working electrode, and cyclic voltammetry electropolymerization is performed at a potential cycle rate of 100 mV / s in a potential range of -0.88 V to +1.10 V vs. SCE. 3,4-ethylenedioxythiophene (EDOT for short) is electropolymerized on the electrode surface to be converted into poly(3,4-ethylenedioxythiophene) (PEDOT for short), forming a composite conductive film.
[0020] The present invention also provides a composite conductive film, which is prepared by the above-mentioned preparation method.
[0021] An application of the composite conductive film prepared as above in electrochemical redox performance, wherein M=Au, Pt, Pd.
[0022] PEDOT / Zn4P4W provided in the embodiment of the present invention 30 @M film preparation method, comprising: Step 1: Preparation of Zn4P4W 30 @M, where M = Au, Pt, Pd; Step 2: In Zn4P4W 30 In the presence of @M, EDOT was electropolymerized to form PEDOT / Zn4P4W on the ITO glass electrode. 30 @M Film.
[0023] PEDOT / Zn4P4W 30 @M film refers to Zn4P4W 30 A conductive film prepared by electropolymerization doping of coated metal M nanoparticles.
[0024] In the embodiment of the present invention, Zn4P4W is prepared 30 @Pt includes the following steps: Step 1: Take 4 mL of a 6.4x10 -5 mol L -1 Zn4(H2O)2(P2W 15 O 56 )2 16- 16Na + (i.e. Zn4P4W 30 ) solution containing 0.5 M isopropanol; Step 2: Add 5 μL of 8 wt.% H2Pt to the above solution. IV C l6 ; Step 3: subjecting the mixed solution to ultrasonic treatment for 20 minutes; Step 4: Subsequently, argon gas was passed into the solution for 30 minutes to remove oxygen therein; Step 5: Irradiate the solution with a UV-visible light lamp and measure the UV spectrum every 20 minutes until the spectrum shows no obvious changes, indicating that the reaction is complete.
[0025] In the embodiment of the present invention, Zn4P4W is prepared 30 @Au includes the following steps: Step 1: Prepare 4 mL of 8x10 -6 mol L -1 Zn4(H2O)2(P2W 15 O 56 )216- 16Na + (i.e. Zn4P4W 30 ) solution containing 0.5 M isopropanol; Step 2: Add 5 μL of HAu with a concentration of 7.4 wt.% to this solution. III Cl4; Step 3: The mixed solution was sonicated for 20 min to ensure uniform mixing; Step 4: Flow argon gas into the solution for 30 minutes to remove oxygen from the solution and create an oxygen-free environment for subsequent chemical reactions.
[0026] In the embodiment of the present invention, Zn4P4W is prepared 30 @Pd includes the following steps: Step 1: Prepare 4 mL of 8x10 -6 mol / L Zn4(H2O)2(P2W 15 O 56 )2 16- 16Na + (i.e. Zn4P4W 30 ) solution containing 0.5 M isopropanol; Step 2: Add 5 μL of 1.28×10 -6 mol / L Pd II SO4 solution; Step 3: Add Pd II The mixed solution after SO4 is subjected to ultrasonic treatment for a period of time (e.g., 20 min) to ensure that Pd II SO4 and Zn4P4W 30 Full contact and response; Step 4: Flow argon gas into the solution for a period of time (e.g., 30 minutes) to remove oxygen from the solution and create an oxygen-free environment for subsequent chemical reactions.
[0027] In the embodiment of the present invention, before the electropolymerization, the method further includes: pre-treating the ITO glass sheet, wherein the ITO glass sheet is ultrasonicated with acetonitrile for 5 minutes, then carefully washed three times with methanol and ultrapure water, and dried in an oven.
[0028] like Figure 1 A) As shown in the figure, the electropolymerization of a single PEDOT film includes: Step 1: Prepare a 5 mmol / LEDOT, pH=1 sulfuric acid solution as the electrolyte for electropolymerization under argon atmosphere at 25°C; Step 2: Immerse the ITO glass sheet in the above electrolyte solution.
[0029] Step 3: Electropolymerization was performed in the potential range of -0.88 V to +1.10 V vs. SCE at a potential cycling rate of 100 mV / s to obtain a single PEDOT film.
[0030] like Figure 1 B) As shown in Figure 2, PEDOT and Zn4P4W 30 Electropolymerization of thin films includes: Step 1: Prepare a 5 mmol / L EDOT, pH=1 sulfuric acid solution under argon atmosphere at 25°C and add Zn4P4W 30 (without metal M nanoparticles) as electrolyte for electropolymerization; Step 2: Electropolymerization was performed in the potential range of -0.88V~+1.10V vs. SCE at a potential cycling rate of 100mV / s to obtain PEDOT / Zn4P4W 30 film.
[0031] PEDOT / Zn4P4W 30 Thin film, refers to Zn4P4W 30 Conductive film prepared by electropolymerization doping.
[0032] like Figure 1 B) As shown in FIG. 1 , the electropolymerization of the present invention comprises: Step 1: Preparation of Zn4P4W by photoinduced method in argon atmosphere at 25 °C 30 @M; Step 2: Zn4P4W 30 @M was dispersed into 5 mmol / L EDOT pH=1 sulfuric acid solution to form Zn4P4W 30 @M electrolyte solution; Step 3: Using the ITO glass sheet or the pretreated ITO glass sheet as the working electrode, electropolymerization was performed at a potential cycle rate of 100 mV / s in the potential range of -0.88 V to +1.10 V vs. SCE to obtain doped Zn4P4W 30 @M's PEDOT film.
[0033] The present invention performs ultraviolet-visible spectrum analysis on the product formed by POMs@M.
[0034] Figure 2 Figures A), B), and C show the concentration of 4 mL 6.4 x 10 -5 mol / LZn4P4W 30 , 5 mL of 8 wt% H2Pt was added to a degassed aqueous solution of 0.5 M isopropanol IV Cl6, Zn4P4W 30@Pt changes in the absorption spectrum during the formation process. Platinum clusters show light scattering and absorption growth around the full wavelength between 150 minutes and 350 minutes, proving that Pt IV Cl4 2- Reduction of anions. Zn4P4W 30 After 350 min of UV irradiation, the absorption increase is due to Zn4P4W 30 The photoreduction of Pt IV Completely restored to pt 0 n Cluster. Complete photoreduction of POM (polyoxometalate), possibly each Zn4P4W 30 Light injects 12 electrons.
[0035] Figure 3 A) Figure, B) Figure, C) Figure show Zn4P4W 30 @Au formed UV-visible spectrum. III Cl4 - In the presence of a single anion, as the illumination time increases, the first plasmon absorption band of the gold cluster is observed, with a maximum value of about 540 nm, indicating that Au III Cl 4- The anions are reduced and the metal atoms condense into Au 0 n clusters and stabilized by POMs as surfactants. Then, Zn4P4W 30 The intervalence band reappeared, with a maximum value close to 670nm. After 440min, the UV-visible spectrum did not change, indicating that the reaction was complete. III Completely reduced to Au 0 n Cluster, Zn4P4W 30 Complete photo restoration.
[0036] same, Figure 4 Shows Zn4P4W 30 Typical UV-Vis spectra during the formation of @Pd. 2+ In the presence of cations, the absorbance of Pd nanoparticles increases with the increase of illumination time, but no specific plasma band appears. 0 n The cluster scattered light appears and the absorption grows. In addition, in this case, Pd 2+The photoreduction of POM was very slow. After 22 hours, an absorption band was observed at around 600 nm for the reduced POM. There was no obvious change in the UV-visible spectrum, indicating that the reaction was complete. 2+ Restore all to pd 0 n Cluster, Zn4P4W 30 Photoreduction. In this case, it is uncertain whether Zn4P4W 30 (12 electrons) because the kinetics of the reaction are very slow and the observed intervalence band maximum is around 600 nm instead of 670 nm. It is well known that the position of the maximum and the intensity of the intervalence band depend on the number of photoinjected electrons.
[0037] The present invention adopts transmission electron microscope to measure Zn4P4W 30 @M performed morphological analysis.
[0038] Zn4P4W 30 @Pt's form is as follows Figure 5 As shown in Figure A) and Figure B), the average particle size is 4.5nm.
[0039] Similarly, TEM images show that Zn4P4W 30 The morphology of @Au shows that the average particle size is 20nm ( Figure 6 The Au nanoparticles are well dispersed without aggregation or precipitation, which may be due to the presence of Zn4P4W 30 As a surfactant, it stabilizes the Au nanoparticles.
[0040] Finally, the morphology of Pd nanoparticles showed similarity to that of Zn4P4W 30 @Au has similar characteristics, but the particle size is smaller: less than 3nm, such as Figure 7 As shown. Zn4P4W 30 @Pd It's also very well dispersed, no clumping.
[0041] The present invention adopts cyclic voltammogram, such as Figure 8 As shown in Figure A, during the electropolymerization of EDOT, an increase in current over the entire potential range was observed during the iterative scan, indicating the formation of a conductive PEDOT film. Specifically, the oxidation current increased at positive potentials indicating that the formation of cationic radicals initiated the polymerization process. This process begins with the formation of EDOT ·+ The formation of radical cationic species then polymerizes. Subsequently, the formed oligomers are also oxidized to form oligomeric radical cations, which in turn react with other EDOT ·+ The deposition of PEDOT polymer on the electrode surface can be indicated by the change of macroscopic color from transparent to blue. Figure 8In Figure B, three specific redox pairs are also observed in the negative part. Compared with the voltammogram of PEDOT, these redox pairs come from Zn4P4W 30 Cluster (W VI / V Yes), indicating that Zn4P4W 30 The clusters were successfully incorporated into the PEDOT polymer chains. These three reduction waves corresponding to the reduction of tungsten atoms were measured at -0.30 V, -0.53 V, and -0.78 V vs. SCE. The results show that the contribution of PEDOT to the overall electrochemical response of POM-doped films is relatively low, and the voltammetric behavior of these films is mainly determined by the redox properties of polyoxometalates.
[0042] Generating doped Zn4P4W 30 @Pt PEDOT polymers such as Fig. 9 A) is shown in Figure 1. During the iterative scan, the current in the full potential range increases, which is characteristic of the conductive polymer layer. Zn4P4W was detected and measured again at -0.30V, -0.53V vs. SCE 30 The two specific redox pairs corresponding to the reduction of tungsten atoms in PEDOT / Zn4P4W 30 @Pt-doped polymer formation. The third peak around -0.78 V cannot be detected due to the HER activity and hydrogen evolution from Pt nanoparticles. Fig. 9 In Figure B, the iterative cyclic voltammogram is clearer, PEDOT / Zn4P4W 30 The difference between each cycle of @Au electropolymerization indicates that a good polymer film was formed on the ITO glass sheet. In this case, no HER activity was observed, and Zn4P4W 30 Three consecutive reductions of were detected again. Doped polymer PEDOT / Zn4P4W 30 @Pd's situation is as follows Fig. 9 Similarly, only the Zn4P4W measured at -0.30V and -0.53V 30 The first two decreases of @Pd exist, while the third wave (doped only with Zn4P4W 30 or Zn4P4W 30 @Au doped film measured at -0.78V) is almost not as good as doped Zn4P4W 30 @Pt polymer. Similarly, only Zn4P4W 30 The two first waves of reduction measured for @Pd at -0.30 V and -0.53 V appear, while the third wave (in the case of Zn4P4W doped only) 30 or Zn4P4W 30 @Au film measured at -0.78V) and doped Zn4P4W 30The same is true for the Pt polymer, which is barely noticeable. In addition, no HER activity was detected.
[0043] The present invention uses UV-visible spectroscopy to track the PEDOT / Zn4P4W 30 Film formation.
[0044] Fig.10 PEDOT / Zn4P4W is shown 30 UV-Vis spectra of polymers versus the number of electropolymerization iteration scans n (n=1 to 10). The absorbance increases with the number of iteration scans n, indicating the growth of the film on the ITO glass sheet. At the electropolymerization iteration scan number n=10, we can observe a band whose maximum at the end rises from 390nm to above 700nm, indicating that Zn4P4W 30 There is an interaction between the cluster and the PEDOT polymer, and the charge is transferred from PEDOT to Zn4P4W 30 Clusters.
[0045] PEDOT polymer and PEDOT / Zn4P4W 30 EQCM (Electrochemical Quartz Crystal Microbalance) during polymer formation: The electrochemical quartz crystal microbalance was used to measure the 30 Weight change during electropolymerization of PEDOT in the presence of clusters. Fig.11 As shown in Figure A and Figure B, in the potential range of -0.88V~+1.10V vs.SCE, the frequency changes successively with 10 iterations of electropolymerization. According to the Sauerbrey equation, after 10 iterations, the PEDOT weight coverage of the PEDOT polymer is 126.6ng, while the Zn4P4W prepared under the same conditions is 30 The PEDOT weight coverage of the / PEDOT polymer is 634.4 ng. The results show that there is Zn4P4W in the PEDOT polymer. 30 Clusters.
[0046] On ITO glass and PEDOT / Zn4P4W 30 Similar conclusions were obtained during the formation of Au thin films.
[0047] Fig.12The surface morphology of the PEDOT film deposited on the ITO glass electrode was obtained by capture mode atomic force microscopy (AFM) after 5 iterations of scanning in the potential range of -0.88V~+1.10V vs.SCE. The cross-sectional analysis of the green line marked on the image under the two-dimensional atomic force microscopy image; The present invention uses the atomic force microscopy (AFM) method to study the PEDOT, PEDOT / Zn4P4W 30 Thin film, PEDOT / Zn4P4W 30 @Pt and PEDOT / Zn4P4W 30 @The film morphology and uniformity of Au thin films. Fig.12 As shown, the PEDOT film shows a uniform plateau with the uniform protrusions typically observed when forming linear polymers on a surface with an average thickness of 20 nm. The RMS roughness of the deposited PEDOT film (obtained after 5 iterative scans) is approximately 11.3 nm.
[0048] Fig.13 The PEDOT / Zn4P4W deposited after 5 iterations of scanning between -0.88V~+1.10V vs.SCE of the present invention 30 Capture mode AFM topography of the film. Profile analysis of the green line marked on the 2D AFM image; PEDOT / Zn4P4W 30 The film morphology is Fig.13 As shown in Figure 2, the size of the protrusions increased significantly and the degree of protrusion aggregation was significant. Fig.12 In comparison, the prepared film exhibits a rough surface. 30 The RMS roughness of the film (obtained after 5 iterations of scanning) is 56.3nm. 30 There is electrostatic interaction between the PEDOT / PEDOT polymers.
[0049] PEDOT / Zn4P4W 30 The film morphology of @Pt is as follows Fig.14 As shown. In the two-dimensional AFM image, the cross-sectional analysis of the green line marked on the image; the prepared film has the same 30 The films have a similarly rough surface, but with better resolution. In this case, the average thickness is about 50nm, and equally important is the aggregation. Deposited PEDOT / Zn4P4W 30 The RMS roughness of the @Pt film (obtained after 5 iterative scans) is 35.9nm.
[0050] Finally, PEDOT / Zn4P4W 30 @The surface morphology of Au film is as follows Fig.15The surface morphology obtained is different from other films. In addition to the usual protrusions, some "volcano"-like microstructures are observed, with an average height of 350nm and a diameter of about 1mm. The "volcano" microstructure is composed of hundreds of small protrusions observed in the background.
[0051] Similar structures were obtained when forming polycationic porphyrin copolymers with organic photosensitizers as spacers. The copolymers coated on the electrode surface had obvious directional arrangement and unexpectedly tightly aggregated into a regular three-dimensional sandwich structure. Further treatment of this well-oriented film with dichloromethane or acetonitrile also led to the uniform dispersion of protrusions on the surface of the ITO glass sheet electrode.
[0052] The formation of volcano-like microstructures can also be explained by the self-alignment of charged protrusions induced by an applied electric field during electropolymerization. In this case, these structures are more robust because the use of acetonitrile treatment does not cause the destruction of the microstructure.
[0053] Photocurrent generation under visible light: Effects of electropolymerization cycles: Fig.16 Shows successive electropolymerization cycles (various iterative scans) of PEDOT / Zn4P4W deposited on an ITO glass sheet electrode. 30 Photocurrent response of the film. PEDOT / Zn4P4W 30 The films were obtained by different electropolymerization iteration scan numbers (n = 1 to 10) at -0.88 V and +1.10 V vs. SCE. Only one side of the glass slide was covered with ITO and illuminated (once every 180 s) with a 300 W Xe lamp (λ ± 385 nm filter). 5 mM I3 - , 0.5MI - Aqueous solution, BIAS potential: -0.1V; Fig.16 As shown, when the illumination is turned on, the film presents a negative photocurrent, and when the illumination is turned off, the photocurrent stops. The reaction is not rapid and takes several seconds to reach the plateau. This result can be explained by the fact that the electron exchange occurs by hopping. It may also be due to the transport of ions related to the movement of charge compensation ions in and out of the film. PEDOT / Zn4P4W 30 The photocurrent performance of the film was measured in the range of n = 1 to 5 (100 mA and cm 2) and then decreases slightly as the number of iterative scans used to prepare the film increases. The same photoelectrochemical trends can be observed with PEDOT films alone. Because electron exchange can occur via hopping, and because ion transport is related to the movement of charge-compensating ions into and out of the film, the conductivity of the film may decrease with decreasing thickness (and the number of iterative scans), thereby reducing the intensity of the photocurrent.
[0054] Zn4P4W 30 The impact of clusters: Fig.17 PEDOT and PEDOT / Zn4P4W are shown 30 At 0.1V bias potential, 5mMI3 - , 0.5MI - Photocurrent performance in aqueous solution. Only one side of the ITO glass sheet was covered and illuminated by a 300W xenon lamp (λ±385nm filter) (once every 180 seconds). Containing 5mMI3 - , 0.5MI - Aqueous solution, BIAS potential: -0.1 V. Black curve: [PEDOT]5 film. Red curve: [PEDOT / Zn4P4W 30 ]5Thin film; PEDOT / Zn4P4W 30 Photocurrent (red curve, Fig.15 , about 100mA / cm 2 ) is about 4 times larger than that of PEDOT film (black curve, Fig.17 , about 30mA / cm 2 ). The results show that in Zn4P4W 30 In the presence of clusters, photocurrent generation under visible light is greatly improved.
[0055] In the present invention, n represents the number of electropolymerization iterative scans. 30 ]5 represents PEDOT / Zn4P4W 30 The film was scanned for 5 electropolymerization iterations.
[0056] Effect of Metal M Nanoparticles: Fig.18 PEDOT, PEDOT / Zn4P4W are shown 30 Thin films and PEDOT / Zn4P4W 30 @M (M=Au, Pt, Pd) film photocurrent comparison. The conductive surface of the ITO glass sheet is covered with polymer and illuminated by a 300W xenon lamp (with λ≥385nm filter) (once every 180 seconds). Contains 5mMI3 - , 0.5MI -Aqueous solution, BIAS potential: -0.1V; Fig.18 As shown, [PEDOT / Zn4P4W 30 @Pt]5 and [PEDOT / Zn4P4W 30 @Au]5 film produces almost the same photocurrent. 30 In the case of [PEDOT / Zn4P4W]5 films, the improvement may be due to light scattering plasmon resonance (LSPR). 30 @Pt]5 does not have a plasma resonance band and has the same 30 @Au]5 film has similar photocurrent intensity. [PEDOT / Zn4P4W 30 The performance of [PEDOT / Zn4P4W 30 @Au]5 film photoresponse ratio [PEDOT / Zn4P4W 30 @Pt]5 Fast, [PEDOT / Zn4P4W 30 @Pt]5 takes more than 180 seconds to reach signal stability. In addition, [PEDOT / Zn4P4W 30 The photocurrent generated by the Pd]5 film was observed to decrease under visible light irradiation.
[0057] The number of electropolymerization cycles n for PEDOT / Zn4P4W 30 @M film influence: Fig.19 A) Figure, B) Figure, C) Figure show [PEDOT / Zn4P4W 30 Photocurrent response of thin films of @M]n nanoparticles (M=Au, Pt, Pd) at different deposition cycles. As the number of iterative scans (i.e., film thickness) increases, the three films doped with metal nanoparticles show similar behavior with increasing photocurrent generation under visible light.
[0058] from Fig.19 In Figures A), B), and C, we can see that in [PEDOT / Zn4P4W 30 @Au] 10 and [PEDOT / Zn4P4W 30 @Pt] 10 The photocurrent measured under visible illumination of the films produced almost the same 30 @Pd] 10 The photocurrent obtained is slightly smaller ( Fig.18 ).
[0059] I3 -Effect of concentration: The photoelectrochemical reaction also depends on the redox mediator, namely triiodide I3 - When there is no I3 in the solution - When the photocurrent density is less than -0.5µA / cm2, the photocurrent density is measured. In this case, the photocurrent vs. time measurement shows an exponential decrease under visible light illumination due to diffusion effects. This indicates a kinetic problem: the film must wait for the I3 formed on the Pt counter electrode to - The arrival of iodide to reoxidize the POM subunit. When the concentration of triiodide increases, the photocurrent increases linearly and increases in [I3 - ] = 15mmol / L. Under these conditions, more triiodide ions reach the modified electrode per unit time and are able to exchange electrons. - At concentrations of 1.3 Å, the photocurrent increases rapidly and reaches a plateau when the xenon lamp is turned on. This is consistent with rapid electron transfer through the film and confirms that diffusion is not a problem. The decrease in photocurrent at higher triiodide concentrations can be explained by the absorption of visible light by the redox mediator itself, such as Fig. 20 As shown in A) and B) (only one side was covered by an ITO glass sheet, illuminated using switched light from a 300W xenon lamp (λ = 385nm filter; BIAS potential: -0.1V;), the number of photons reaching the film was reduced.
[0060] In [PEDOT / Zn4P4W 30 Similar observations were also made in the [I3 - ] Cohesion effect, such as Fig.21 As shown in A) and B), only one side is covered by an ITO glass sheet and illuminated by a 300W xenon lamp (with a λ≥385nm filter) (once every 180 seconds); BIAS potential: -0.1V. - ]=15mM. 30 Similar results were obtained in Pd]5 thin films.
[0061] In summary, a novel [PEDOT / Zn4P4W 30 @Pt]n (M = Au, Pt, Pd) thin films. Cyclic voltammetry, UV-visible spectroscopy, atomic force microscopy, and X-ray photoelectron microscopy have demonstrated the formation of conductive hybrid films. 30 The clusters are fixed in the PEDOT hybrid film, which improves the electrochemical redox performance of PEDOT. - with I- Photocurrent performance in aqueous solution shows a particularly important enhancement in photocurrent generation under visible light compared to a single PEDOT film. The present invention discloses polyoxometalate materials doped with PEDOT that exhibit significant potential for generating photocurrent as working electrodes in aqueous solution.
[0062] In the embodiment of the present invention, a novel PEDOT / Zn4P4W 30 @M thin film [Zn4P4W 30 =Zn4(H2O)2(P2W 15 O 56 )2 16- 16Na + and M = Au, Pt, Pd], and PEDOT / Zn4P4W 30 The film is prepared by Zn4P4W 30 @M or Zn4P4W 30 PEDOT was electropolymerized in the presence of . The conductive hybrid film was characterized and studied by cyclic voltammetry, UV-visible spectroscopy, AFM, XPS and ATR-FTIR. 30 The clusters are immobilized in the PEDOT hybrid membrane, which improves the redox performance of PEDOT in electrochemical applications. - with I - The prepared PEDOT / Zn4P4W 30 The photocurrent performance of the @M film was compared with that of pure PEDOT. This work demonstrates the potential of polyoxometalate-doped PEDOT as a working electrode for photocurrent generation in aqueous solution.
Claims
1. A method for preparing a composite conductive film, characterized in that: include: Step 1: Preparation of Zn4P4W 30 The solution was added with a metal salt solution of metal M, ultrasonically treated and argon was introduced, and a Zn4P4W-coated surface was prepared under ultraviolet light. 30 Metal M nanoparticles; Step 2: At a certain temperature, in an argon environment, 3,4-ethylenedioxythiophene is converted into poly (3,4-ethylenedioxythiophene) on the ITO glass sheet electrode through an electropolymerization reaction in an electrolyte solution to form a composite conductive film. The conductive film is formed by using Zn4P4W 30 The enclosed metal M nanoparticles are formed by the electropolymerization doping process; The conditions of the electropolymerization reaction are -0.88V~+1.10V vs. SCE, and the electropolymerization is carried out at a cycle rate of 100mV / s; the electrolyte solution is a sulfuric acid solution with a pH=1; and the metal M=Au, Pt, Pd.
2. The method according to claim 1, characterized in that Preparation of Zn4P4W 30 The solution includes: According to the type of metal M, prepare 4mL of Zn4P4W with corresponding concentration. 30 A solution containing 0.5 M isopropanol.
3. The method according to claim 2, characterized in that When metal M=Pt, Zn4P4W 30 The concentration of the solution is 6.4x10 -5 mol / L; when metal M=Au, Zn4P4W 30 The concentration of the solution is 8x10 -6 mol / L; when metal M=Pd, Zn4P4W 30 The concentration of the solution is 8x10 -6 mol / L.
4. The method according to claim 1, characterized in that: The metal salt solution to which metal M is added includes: when metal M=Pt, to Zn4P4W 30 Add 5 μL of 8 wt.% H2Pt to the solution. IV C l6 ; When metal M = Au, to Zn4P4W 30 Add 5 μL of HAu with a concentration of 7.4 wt.% to the solution III Cl4; when metal M=Pd, it moves to Zn4P4W 30 Add 5 μL of the solution with a concentration of 1.28×10 - 6 mol / L Pd II SO4 solution.
5. The method according to claim 1, characterized in that The ultrasonic treatment time was 20 minutes.
6. The method according to claim 1, characterized in that The argon gas was introduced for 30 minutes.
7. The method according to claim 1, characterized in that Before the electropolymerization reaction, the method further includes: pre-treating the ITO glass sheet; The ITO glass sheet was pretreated as follows: the ITO glass sheet was ultrasonicated with acetonitrile for 5 minutes, then carefully washed with methanol and ultrapure water three times, and dried in an oven.
8. The method according to claim 1 or 5, characterized in that: The electropolymerization reaction comprises: Step 1: Prepare a Zn4P4W-coated substrate by photoinduction in an argon atmosphere at 25°C. 30 Metal M nanoparticles; Step 2: Cover the surface with Zn4P4W 30 The metal M nanoparticles are dispersed into a sulfuric acid solution with a pH of 1 to form an acidic electrolyte solution containing the nanoparticles; Step 3: In the electropolymerization reaction, an ITO glass sheet or a pretreated ITO glass sheet is used as a working electrode, and cyclic voltammetry electropolymerization is performed at a potential cycle rate of 100 mV / s in a potential range of -0.88 V to +1.10 V vs. SCE. 3,4-ethylenedioxythiophene is electropolymerized on the electrode surface to be converted into poly(3,4-ethylenedioxythiophene), forming a composite conductive film.
9. A composite conductive film, characterized in that: The composite conductive film is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite conductive film prepared according to any one of claims 1 to 8 in electrochemical redox performance.
Citation Information
Patent Citations
Method for directly preparing poly (3,4) dioxoethyl-thiophene film on surface of conductive glass
CN101781094A
A polyaniline nanoribbon composite and its preparation method
CN102276831A
Polymer-polyoxometalate composite material and preparation method and application thereof
CN106611818A
Secondary doped carbon nanotube transparent conductive film and preparation method thereof
CN116230294A
A process for electrochemical deposition of pedot and its derivate as HTL useful in organic solar cells
IN201611027796A